The Influence of Work-Life Balance, Burnout, and Job Satisfaction on Intention to Stay on Generation Z Employees in Surakarta City - Audiya Khilya Wardah; Helmi Haris (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
Generation Z has a different way of working; an imbalance can reduce performance at work. Work-life balance is essential to maintain employee productivity, especially Generation Z employees. Employees who get job satisfaction will feel comfortable and productive and want to stay in the company. This study aims to determine the Effect of Work-Life Balance, Burnout, and Job Satisfaction on the Intention To Stay with Generation Z Employees in Surakarta City.   This study uses a quantitative approach using non-random sampling techniques, namely purposive sampling, where samples are taken based on specific criteria.   The data collection process used a questionnaire with Likert scale measurements and a sample of 96 respondents. Data analysis was carried out with the help of statistical software, namely SPSS version 25. The results showed that variable (X1) work-life balance significantly and positively affects variable (Y) intention to stay, variable (X2) burnout significantly and does not have a positive effect on variable (Y) intention to stay, and variable (X3) job satisfaction significantly and positively affects variable (Y) intention to stay.